Governance in Multilateral R&D Alliances - Li, Dan; Eden, Lorraine; Hitt, Michael A.; Ireland, R. Duane; Garrett, Robert P. (Organization Science, 2012)
In research and development (R&D) alliances, the partner firms must balance the tension between knowledge sharing and knowledge leakages because knowledge sharing, designed to support the alliance's technology development goals, can often lead to unintended and potentially damaging knowledge leakages. Governance structure is a well-understood knowledge protection strategy designed to reduce knowledge leakage concerns and thereby encourage desired knowledge transfers in two-party R&D alliances. Whether governance structure can be an important balancing mechanism for R&D alliances with multiple partner firms, or multilateral R&D alliances, however, requires further study. Because increasing the number of alliance partners introduces additional complexities to managing an alliance, the appropriate governance mechanism for a multilateral R&D alliance is likely to differ from that for a bilateral alliance. Drawing insights from social exchange theory, we explore governance decisions in multilateral R&D alliances. First, we examine the potential for variance between multilateral and bilateral R&D alliances in governance decisions as a means of knowledge sharing and knowledge protection. Results based on our analysis of 2,423 R&D alliances, 1,690 bilateral and 733 multilateral, are consistent with predictions drawn from social exchange theory. We next focus on three-partner R&D alliances, or trilateral R&D alliances, and compare governance mechanisms between two types of trilateral R&D alliances: chain and net. We find that equity governance structures are more likely to be used in net-based than in chain-based trilateral R&D alliances; we also find that alliance scope moderates the relationship between the type of alliance and governance structure. Finally, we find that multilateral R&D alliances with predicted (aligned) governance structures perform better, in terms of alliance longevity, than those with misaligned structures.